DISEASES DURING CAMPING IN BNCC - Kabir, M Ashraful; M Harun (International Journal of Research -GRANTHAALAYAH, 2017)
During camping in BNCC all cadets face some medical problems. Their problems not more worsen but this may lead misunderstanding about the training of BNCC. Our cadets are normally fit because when they get admitted in BNCC there was a criterion that they are medically fit or not. The major problems such as asthma, big birth defect, nasal and ear problems not allowed in BNCC. In camping they get excellent medical services so that they not fall serious problems. In BNCC camping cadets get always fresh food and water and moreover they take bathe regularly. After march past or exercise they take oral saline, so not shown any dehydration. Some simple injuries for wearing tight shoes and for crawling knee and elbow injury are common. All trainings are held in winter season so for cold weather their exercise not considered burden. Cadets sweating are very few so they get more energy in training. In noon they perform playing and every night the cultural show rehearsal runs. Mostly all cadets live well any camping without any major diseases. The writers of this paper both they attend several camping with high ages but not got any major diseases during camping (Plate 4).